Strategic Prioritization for Sustainable Urban Tourism in Bandung Raya: An Analytical Hierarchy Process Approach - Jayanti, Lilis; Mukti, Reno Anggara (Politeknik Negeri Bandung, 2025)
Urban tourism has become a key driver of economic and spatial transformation in many cities of the Global South, including Bandung Raya, Indonesia. While tourism offers substantial opportunities for cultural revitalization and economic growth, it also imposes pressures on infrastructure, mobility, and local communities. This study aims to identify and prioritize sustainable urban tourism strategies for Bandung Raya using the Analytical Hierarchy Process (AHP), a multi-criteria decision-making method that integrates expert judgment and structured prioritization. Drawing on input from 15 experts representing government, academia, industry, and civil society, the research evaluates five alternative strategies—heritage revitalization, smart mobility systems, digital tourism platforms, community-based tourism (CBT), and green urban infrastructure—across five sustainability criteria: accessibility, infrastructure, tourist attractions, community engagement, and environmental sustainability. The results indicate that heritage revitalization ranks highest, followed by smart mobility systems and digital tourism platforms, reflecting the perceived importance of Bandung's cultural identity and accessibility challenges. Conversely, CBT and green infrastructure, while scoring well under specific criteria, ranked lower globally due to the lower weight assigned to social and environmental dimensions. The findings highlight the need to balance short-term priorities with long-term sustainability goals and suggest the utility of AHP as a decision-support tool for inclusive and strategic urban tourism planning. The study offers actionable insights for policymakers and contributes to the broader discourse on sustainable urban tourism in developing city contexts.